Evaluasi Program Penataan dan Pemberdayaan Pedagang Kaki Lima di Kota Makassar - Reviva Fachrunisa; Gita Susanti; Andi Ahmad Yani (Development Policy and Management Review (DPMR), 2021)
Research on evaluating the arrangement and empowerment of street vendors (Case Study: Kanrerong Program in Makassar City) aims to determine the evaluation of the implementation of the Kanrerong Karebosi street vendor arrangement and empowerment program in Makassar city. The theory used for this research is the theory of public policy evaluation. The research method used is descriptive research method with a qualitative approach. Sources of data obtained from primary data and secondary data. The research location is in the Office of Cooperatives and Small and Medium Enterprises and the Culinary Tourism area of Kanrerong Karebosi. Data collection techniques using interviews, observation, and documentation. The results showed that the evaluation of the implementation of the Kanrerong street vendor arrangement and empowerment program in the city of Makassar had not shown the maximum effectiveness, efficiency, adequacy, equity, responsiveness and accuracy of the Kanrerong Karebosi street vendor arrangement and empowerment program in Makassar City. The results of the study indicate that the Kanrerong program is not running as expected and what is to be achieved. For this reason, researchers provide facilities to further maximize and run the Kanrerong program, especially for the empowerment of street vendors who have been relocated so that they can run according to the goals set by the Makassar City Government.